2021
DOI: 10.3390/horticulturae7120560
|View full text |Cite
|
Sign up to set email alerts
|

Rhizospheric Fungal Diversities and Soil Biochemical Factors of Fritillaria taipaiensis over Five Cultivation Years

Abstract: Fritillaria taipaiensis is a valuable traditional Chinese medicinal plant that has experienced continuous decline over its cropping area. The present study aims to explore the reasons for the quality and growth decline. The fungal diversities and biochemical factors in its rhizospheric soils with cultivation duration from 1 up to 5 years were analyzed and compared. The results showed that rhizospheric fungi of F. taipaiensis belong to six phyla, including Neocallimastigomycota, Glomeromycota, Basidiomycota, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The results of UPGMA, NMDS and Adonis showed that the bacterial community structures in the soils with the adjacent cultivation years were closer to each other in clustering, which indicated that the bacterial community structure in F. taipaiensis rhizospheric soil changed gradually rather than suddenly with the cultivation year. Long-term single planting is considered as a process of pathogen accumulation and soil nutrient status deterioration 26 . The dominant bacterial genera in Y1 were mainly the species that could degrade organic carbon to promote the organic cycling in soil or participate in soil nutrient cycling and the species could produce secondary metabolites to protect plants from diseases or promote the growth of plants: Haliangium produces haliangicin that can inhibit the growth of a wide spectrum of fungal pathogen 29 ; Ferruginibacter and Chthoniobacter play important roles in soil carbon mineralization and carbohydrate metabolism 30,31 ; species in genus Piscinibacter are methylotrophic bacteria that participate in the soil carbon cycle to increase organic matter in soil 32 ; Germmatimonas is one of the most dominant groups in agricultural ecosystems that take part in nitrogen metabolism 33 ; Opitutus is strongly positive correlate with NO 3− -N in the soil 34 ; Arenimonas species have catalytic activities of phosphatase and multiple lipases 35 ; Bacteroides has the capability to produce acid that can dissolve minerals and provide nutrients for plants 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of UPGMA, NMDS and Adonis showed that the bacterial community structures in the soils with the adjacent cultivation years were closer to each other in clustering, which indicated that the bacterial community structure in F. taipaiensis rhizospheric soil changed gradually rather than suddenly with the cultivation year. Long-term single planting is considered as a process of pathogen accumulation and soil nutrient status deterioration 26 . The dominant bacterial genera in Y1 were mainly the species that could degrade organic carbon to promote the organic cycling in soil or participate in soil nutrient cycling and the species could produce secondary metabolites to protect plants from diseases or promote the growth of plants: Haliangium produces haliangicin that can inhibit the growth of a wide spectrum of fungal pathogen 29 ; Ferruginibacter and Chthoniobacter play important roles in soil carbon mineralization and carbohydrate metabolism 30,31 ; species in genus Piscinibacter are methylotrophic bacteria that participate in the soil carbon cycle to increase organic matter in soil 32 ; Germmatimonas is one of the most dominant groups in agricultural ecosystems that take part in nitrogen metabolism 33 ; Opitutus is strongly positive correlate with NO 3− -N in the soil 34 ; Arenimonas species have catalytic activities of phosphatase and multiple lipases 35 ; Bacteroides has the capability to produce acid that can dissolve minerals and provide nutrients for plants 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Predominantly, soil fungal community analysis has focused on internal transcribed spacer (ITS) markers [42,47,51,52,[64][65][66][67][68][69], while chytrid aquatic fungal community diversity has been elucidated by targeting the 18S rRNA gene marker [41,70,71]. Non-Dikarya lineages are at a particular disadvantage due to the lack of information about the diversity within various groups [72], and the suitability of current markers is, therefore, likely hampered.…”
Section: Chytrid Presence and Diversity In Soilsmentioning
confidence: 99%
“…And Ascomycota fungi were the most dominant population. With the increase in planting years, the relative abundance of Pseudogymnomyces in the soil rhizosphere gradually decreased, along with the relative abundance of populations such as pathogenic fungi in Fusarium , Gibberella , Rhizopus , Colletotrichum , and Peziza ( Mu, 2019 ; Zhou et al, 2021 ).…”
Section: Diversity Of Rhizosphere Microorganisms Associated With Medi...mentioning
confidence: 99%